Analysis of patellar reflex in Parkinson disease patients after an acupuncture treatment protocol – Case series study - Catarina Ramos Pereira; Jorge Machado; Begoña Criado; Rubim Santos; Ana Mafalda Reis; Bruno Ramos; Maria João Santos; Henry Johannes Greten (Clinical Parkinsonism & Related Disorders)
Introduction: The investigation of rigidity physiology in Parkinson’s Disease involves the examination of reflexes. Parkinsonian patients often demonstrate reduced sensitivity in polysynaptic reflexes within the leg extensor muscles, which is correlated with their postural instability. The compensatory mechanisms for impaired proprioceptive reflex function may involve alterations in intrinsic muscle stiffness. The interplay between gait and reflexes is intricately linked to the nervous system’s functioning and motor control. Certain reflexes, such as patellar reflex, play a pivotal role in maintaining walking and posture. Ensuring the integrity of these reflexes is essential for facilitating smooth and efficient walking. Aim: To analyze the behavior of patellar reflex in four Parkinson’s Disease patients undergoing an acupuncture treatment protocol. Methods: This study adopts a case series design. Reflex outcomes based on amplitude and velocity were assessed at six different time moments throughout a month-long treatment protocol using the MP 36, Biopac Systems. Results: Over the long term, a tendency for an improvement in range of movement and velocity of the patellar reflex, was observed. Nevertheless, in specific cases, a reduction in the amplitude during acute effects was also found. Conclusion: Our findings suggest that the acupuncture protocol used may lead to a cumulative improvement in efficacy of patellar reflex in patients with Parkinson’s disease. However, further in-depth research, including a statistical evaluation with a larger participant pool, is necessary to validate and confirm these promising preliminary results.